Closing Auctions and Price Discovery: Investigating the Role of Index Funds and Their Influence on Market Liquidity - Ruslaini, Ruslaini; Rizal, Muhammad; Permana, Ngadi (International Journal of Management, Accounting & Finance (KBIJMAF), 2024)
This qualitative literature review explores the role of closing auctions in price discovery and the influence of index funds on market liquidity. By analyzing recent empirical studies, the review reveals that closing auctions serve as vital mechanisms for aggregating market information, thus facilitating accurate price formation. The presence of index funds significantly enhances market liquidity during these auctions, contributing to increased trading volumes and price stability. However, the findings also indicate a complex relationship, as index fund activities can lead to increased volatility in turbulent market conditions. This dual impact underscores the need for market participants, including traders and regulators, to closely monitor index fund behavior during closing auctions. The review highlights the evolving landscape of financial markets and emphasizes the importance of understanding how these elements interact within the broader ecosystem. While the research provides valuable insights, limitations such as selection bias and methodological variability are acknowledged, suggesting areas for future research. Overall, this review contributes to a deeper understanding of the interplay between closing auctions and index funds, informing stakeholders about the implications for market efficiency and stability.